41-Week Study of Progressive Diabetic Nephropathy in the ZSF1 fa/faCP Rat Model. (December 2018) - Homer, Bruce L.; Dower, Ken
This symposium synopsis summarizes key results from a 41-week study of diabetic nephropathy (DN) in the type 2 diabetic ZSF1 fa/fa CP rat model. During this study, we conducted longitudinal analysis of biomarkers, renal histopathology, ultrastructural assessment, renal quantitative image analysis, and transcriptome analysis of glomerular-enriched tissue. We concluded that there is translational value for using the ZSF1 rat model in mechanistic and therapeutic intervention efficacy studies for type 2 DN.